KOMBINASI MODEL PEMBELAJARAN: (Problem-Based Learning, Team Game Tournaments, Talking Stick) - Rahmi Yanti; Ramadi (ISTIQRA: Jurnal Hasil Penelitian, 2024)
The "PROTEIN" learning model is a combination of three learning models, namely problem-based learning, team game tournaments, and talking sticks, which aims to encourage maximum active participation of teachers and students in increasing students' motivation and speaking skills in participating in beautiful Indonesian language learning theme seven the diversity of my country. This research uses qualitative methods with the type of classroom action research. The data sources for this research were Indonesian language teachers and 20 class 4 A students, with 11 male students and nine female students. The data collection techniques used in this research are tests, observations, questionnaires, and documentation. Observations carried out in the study are in the form of teacher and student activities. Based on the results of data analysis at four teacher activity meetings, it went well and was successful. Meanwhile, participants' activities were trained in 4 meetings. It was seen that the percentage of activity increased in each meeting. These activities indicate that students' learning motivation in learning speaking skills in Indonesian subjects using a combination of the "PROTEIN" model has reached the criteria of being highly motivated. For learning outcomes, they achieved complete classical and individual learning outcomes with very high criteria. Based on the research results above, the researcher recommends that the combination of the "PROTEIN" learning model be applied in elementary schools. For more effective implementation, teachers need to be given more training so that the application of the combination of the "PROTEIN" learning model can run effectively and efficiently.